2020
DOI: 10.7554/elife.59976
|View full text |Cite
|
Sign up to set email alerts
|

Distinct subpopulations of mechanosensory chordotonal organ neurons elicit grooming of the fruit fly antennae

Abstract: Diverse mechanosensory neurons detect different mechanical forces that can impact animal behavior. Yet our understanding of the anatomical and physiological diversity of these neurons and the behaviors that they influence is limited. We previously discovered that grooming of the Drosophila melanogaster antennae is elicited by an antennal mechanosensory chordotonal organ, the Johnston's organ (JO) (Hampel et al., 2015). Here, we describe anatomically and physiologically distinct JO mechanosensory neuron subpopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 78 publications
3
26
0
Order By: Relevance
“…JOs detect diverse types of mechanical forces and send their projections into discrete zones in the AMMC. 30 EM reconstruction showed that the majority of JOs that connect to JO-in belong to the JO-E subtype, which are thought to detect static deflection of the antenna. 31,32 Since the JO-E neurons were previously shown to connect directly or indirectly to aDNs and their activation induces antennal grooming 14,23 (Figure S4B), we were puzzled to find them upstream of the DNg11 neurons that induce the competing behavior of front leg rubbing.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…JOs detect diverse types of mechanical forces and send their projections into discrete zones in the AMMC. 30 EM reconstruction showed that the majority of JOs that connect to JO-in belong to the JO-E subtype, which are thought to detect static deflection of the antenna. 31,32 Since the JO-E neurons were previously shown to connect directly or indirectly to aDNs and their activation induces antennal grooming 14,23 (Figure S4B), we were puzzled to find them upstream of the DNg11 neurons that induce the competing behavior of front leg rubbing.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…GRNs from the proboscis labellum send axons through the labial nerve to the SEZ (Figure 1A). The labial nerve is a compound nerve, carrying sensory axons from the labellum, maxillary palp, and eye, as well as motor axons innervating proboscis musculature (Hampel et al 2020, Hartenstein et al 2018, Miyazaki & Ito 2010, Nayak & Singh 1983, Rajashekhar & Singh 1994). Different sensory afferents occupy different domains in the SEZ, with labellar gustatory axons terminating in the anterior central sensory center (ACSC) (Hartenstein et al 2018, Miyazaki & Ito 2010, Thorne et al 2004, Wang et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…In the adult olfactory system, approximately 40% of the input onto olfactory receptor neurons (ORNs) comes from other ORNs projecting to the same olfactory glomerulus (Horne et al 2018, Schlegel et al 2021, Tobin et al 2017). Similarly, mechanosensory projections from the Johnston’s Organ of the same submodality are anatomically segregated and synaptically connected (Hampel et al 2020). In Drosophila larvae, 25% of gustatory neuron inputs are from other GRNs, although functional classes were not resolved (Miroschnikow et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations